To solve the equation, start by distributing the 3 to the terms inside the parentheses:
1/(18x-27) = -33
Next, multiply both sides of the equation by the denominator of the fraction (18x-27) to eliminate the fraction:
(18x-27) * (1/(18x-27)) = -33 * (18x-27)
This results in:
1 = -33 * (18x-27)
Simplifying the right side of the equation:
1 = -594x + 891
Move the constant term to the left side:
594x = 890
Finally, divide both sides of the equation by 594 to solve for x:
x = 890/594
x = 1.4966 (rounded to 4 decimal places)
Solve for x.
1 over 3(6x−9)=−33
1 answer